Stress concentration analysis of plate with circular hole : elasticity theory and finite element comparison - Masrol, S.R.; Siswanto, W.A. (Trans Tech Publications, 2014)
Stress concentration factor for a plate with circular free stress hole subjected to a uniform far field tension in single was investigated in this study. The stress concentration level along X and Y axis was determined by the elasticity theoritical method. Finite element analysis using LISA free source software was validate by the elasticity theoritical results. It was found that finite element analysis stress concentration factor results shows similar pattern as theoretical but higher near of the hole. Plain strain analysis with Quad 8 element type showed better results compared to plain stress with Quad 4 element type and plain strain with Quad 4 element type.